Current Status and Challenges of Support Environments for New Graduate Occupational Therapists in Japanese Hospitals: A Mixed Method Study - Shigehito Shiota; Naoya Goto; Aki Kanayama; Yuko Kubo; Kazuhiko Hirata; Yoshihiro Ito; Hiroaki Kimura (Occupational Therapy International)
Introduction. The number of occupational therapists in Japan continues to increase, which has led to an urgent need to improve the educational environment for new graduate occupational therapists. This study attempted to identify the current state and challenges of the educational environment for new graduate occupational therapists in Japan. Methods. We employed a mixed method using quantitative and qualitative data from a questionnaire survey of 1055 chief occupational therapists in Japanese hospitals. The questionnaire consisted of (1) basic information about the respondent and their hospital, (2) educational environment for new graduate occupational therapists at the respondent’s hospital, (3) time spent on in-hospital lectures and on-the-job training, and (4) challenges in the clinical education of new graduate occupational therapists. Text data was analysed qualitatively using text mining to create cooccurrence networks. Results. A total of 385 responses were obtained with a response rate of 36.5%. All hospitals had recruited new graduate occupational therapists in the last five years, but more than half of them did not have a philosophy and policy on education and had not prepared guidelines for the completion of occupational therapy education. The cooccurring network of issues in the educational environment for new graduate occupational therapists indicates the need to create standard guidelines, train supervisors, and develop a hospital education system. Conclusion. In the future, the needs of the educational environment for newly graduated occupational therapists should be investigated, and standardised educational guidelines should be developed.